The Industrial Application of Statistical Quality Control by Homer M Sarasohn : a Historical Perspective by W H Woodall. - Fisher, Nicholas (John Wiley & Sons, Incorporated, 2018)
Professor Woodall's essay shows that this book represents a remarkable contribution, even by today's standards, because of its contemporary thinking about the relationship between the specific topic of SQC and the broader company context of Quality Management. It also demonstrates the remarkable awareness of at least some young US engineers in the post-war period about the vital role of Statistical Quality Control in establishing and maintaining a competitive position. The book reveals that there was unsuspected knowledge extant immediately post-war, about the importance of Statistical Quality Control when appropriately applied in an industrial setting. It also helps to correct wide-spread historical misconceptions about who specifically was responsible for helping Japanese industry get back on its feet post-war, a task assigned to General Douglas Macarthur by President Truman and how Macarthur was indebted to Sarasohn.